Clinico‐pathological correlation of optical fluorescence imaging in oral mucosal lesions. (21st April 2020) - Tiwari, Lalima; Kujan, Omar; Farah, Camile S.
Abstract: Objectives: This study aimed to identify clinical and pathological characteristics of oral mucosal lesions that may be predictive of optical autofluorescence imaging patterns. Methods: Clinical data and archival histopathological material were collected from patients who presented with at least one oral mucosal lesion and underwent assessment via conventional oral examination, optical autofluorescence imaging and histopathological analysis. An open‐source digital pathology image analysis software was used to perform histomorphometric measurements. Classification and regression trees were used to determine histopathological characteristics most predictive of a clinical autofluorescence outcome. Results: Histomorphometric features associated with tissue architecture, epithelial changes, inflammation and vasculature were found to be significantly associated with autofluorescence patterns. Diascopic fluorescence was found to be significantly predicted by lichenoid inflammation and was significantly associated with a diagnosis of oral lichen planus. Loss of autofluorescence with partial blanching was significantly associated with histopathological features noted in dysplastic and malignant lesions. Conclusions: This study provides evidence for the use of diascopic fluorescence as a technique to aid in clinical differentiation of benign inflammatory lesions from potentially malignant pathology. Based on the findings of this study, optical fluorescence imaging is a technique of added value in discernment of oral mucosal lesions, and our results support its clinical use.